2022
DOI: 10.1186/s43159-021-00147-y
|View full text |Cite
|
Sign up to set email alerts
|

Jejunoileal atresia: a case-series of 63 neonates and risk factors to mortality

Abstract: Introduction Jejunoileal atresia (JIA) among neonates is still a condition which has huge morbidity and mortality, particularly in the developing world. We share a case series of JIA in context of their presentation, management, and outcome. Materials and methods This study was conducted at Children’s Hospital and Institute of Child Health, Lahore, over 1 year. We included all patients presenting with JIA, and their demographic details, presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
0
1
1
Order By: Relevance
“…The average time for symptoms to appear in our patients was 3.85 days, which is in agreement with most previous studies. 24 , 25 However, our results were contrary to the study reported by Cairo et al, wherein most of the babies presented with intestinal atresia after 7 days of age. 26 This indicates that the onset of presentation in intestinal obstruction is early and it is necessary to pay attention to symptoms, otherwise, it will lead to rapid deterioration of the baby’s condition.…”
Section: Discussioncontrasting
confidence: 99%
“…The average time for symptoms to appear in our patients was 3.85 days, which is in agreement with most previous studies. 24 , 25 However, our results were contrary to the study reported by Cairo et al, wherein most of the babies presented with intestinal atresia after 7 days of age. 26 This indicates that the onset of presentation in intestinal obstruction is early and it is necessary to pay attention to symptoms, otherwise, it will lead to rapid deterioration of the baby’s condition.…”
Section: Discussioncontrasting
confidence: 99%
“…A suspeição diagnóstica durante o pré-natal pode ser feita através da identificação de alças intestinais dilatadas (múltiplas bolhas) e polidrâmnio em ultrassonografia obstétrica. Também podem se apresentar com peritonite meconial e perfuração perinatal 5 . No período pós-natal a investigação diagnóstica pode ser iniciada através de radiografia simples do abdome, enema de contraste e estudo ultrassonográfico.…”
Section: Introductionunclassified